Molecular point-of-care testing for chlamydia and gonorrhoea in Indigenous Australians attending remote primary health services (TTANGO): a cluster-randomised, controlled, crossover trial. Issue 10 (October 2018) - Guy, Rebecca J; Ward, James; Causer, Louise M; Natoli, Lisa; Badman, Steven G; Tangey, Annie; Hengel, Belinda; Wand, Handan; Whiley, David; Tabrizi, Sepehr N; Shephard, Mark; Fairley, Christopher K; et al.
Summary: Background: Timely diagnosis and treatment of sexually transmissible infections will prevent morbidity and onward transmission. We aimed to assess the efficacy of a point-of-care molecular test for Chlamydia trachomatis and Neisseria gonorrhoeae infections at the cluster level to improve infection management among Indigenous Australian communities with high prevalence of sexually transmissible infections. Methods: In this cluster-randomised crossover study, we recruited primary health services in Western Australia, Far North Queensland, and South Australia that provide care to Indigenous people in regional or remote locations. The services were eligible if they did 150 or more tests for C trachomatis or N gonorrhoeae infection per year among individuals aged 16–29 years, and if C trachomatis or N gonorrhoeae positivity was 10% or higher. Services were randomly assigned (1:1) by use of a random-number generator, stratified by geographical region, to either standard care conditions with routine laboratory-based sexually transmissible infection testing for 12 months followed by 12 months of intervention with molecular point-of-care testing, or the reverse sequence. The primary outcome was the proportion of people (aged 16–29 years) found to have C trachomatis or N gonorrhoeae who had a positive result at retesting 3 weeks to 3 months after treatment, and a secondary outcome was treatment within 7 days, both in those aged 16–29 years and at the cluster level. We did these analyses using data from all participants who had a positive result at testing, by point-of-care of laboratory testing (ie, the intention-to-treat population). The trial is registered with Australian and New Zealand Clinical Trials Registry (ACTRN12613000808741). Findings: Between June 1, 2013, and Feb 29, 2016, 12 health services were enrolled and randomly assigned to standard care followed by intervention (six) and the reverse sequence (six). After randomisation, one health service that was initially assigned to standard care was excluded because it no longer met the inclusion criteria. 455 individuals tested positive for C trachomatis or N gonorrhoeae infection in the intervention group, and 405 tested positive in the standard care group. In the intervention group, 12 (19%) of 63 individuals retested had a positive test result, compared with nine (13%) of 67 with positive retests in the standard care group (relative ratio [RR] 1·42, 95% CI 0·64–3·13; p=0·405), and 347 (76%) were treated within 7 days in the intervention group, compared with 191 (47%) in the standard care group (RR 1·66, 1·41–1·93; p<0·0001). Interpretation: Retesting rates were too low to draw conclusions on the effect of the intervention on repeat infections. Further research will be needed to determine whether point-of-care tests have an effect on reinfection rates, and the sustainability of using this technology. However, our findings show that time to treatment of C trachomatis or N gonorrhoeae infections in primary care clinics in remote areas in Australia with a high prevalence of sexually transmissible infections could be substantially reduced by the use of molecular point-of-care tests. Funding: The National Health and Medical Research Council, Australia